Combined Non-Invasive Cardiac Imaging and Genetic Testing of Elite Volleyball Players: A Ten-Year Experience - Grossfeld, Paul (Cardiology and Cardiovascular Medicine, 2021)
Sudden cardiac death in athletes is a devastating event. Although significant progress has been made in identifying the underlying pathophysiology and genetic basis for sudden cardiac death in young athletes, controversy exists regarding cost-effective screening measures to identify at-risk individuals. In this report we describe our ten-year experience performing cardiovascular assessments on 150 members of the United States Men’s and Women’s National Volleyball teams. Through a combination of history, physical, echocardiography and genetic testing, we have identified one previously undiagnosed athlete with Marfan syndrome, along with four others with a possible aortopathy. Taken together, this approach is a cost-effective strategy for the identification of at-risk tall athletes leading to potentially lifesaving interventions, and raises the issue of the feasibility of screening for all tall individuals.